Optimization of Pipe Production Scheduling in Line 18 Using First Come First Serve (Fcfs), Earlier Due Date (Edd), Short Process Time (Spt) Methods (Case Study: Pt Wtur) - Mohamad Rizal Fadli; Wiwik Sulistiyowati (Universitas Muhammadiyah Sidoarjo, 2019)
For machine line 18, is intended to produce PVC pipe with a 5